ISO 14001 Environmental Management System Approvals In the economic institutions in Algeria - Maazouz, moukhtar; Allab, Rachid (Dirassat Journal Economic Issue, 2016)
Recent decades have seen the emergence and development of various managerial practices that respect quality and the environment. However, analysis of the reasons for adopting these managerial practices by companies and their impact on businesses has been little studied by economists. The aim of this empirical study is to identify the factors that push economic companies in Algeria to adopt ISO 14001 standards. We analyze a logistic regression model that describe the relationship between several determinants and the adoption of ISO 14001 standards, using various variables that may impact the adoption of ISO 14001 standards by economic companies in Algeria. We conclude that the companies oriented to Export and that have a large business as also that transact with oil companies are more oriented to adopt ISO 14001 standards.